Impaired microvascular circulation in distant organs following renal ischemia. - Jesus H Dominguez; Danhui Xie; K J Kelly (PLoS ONE)
Mortality in acute kidney injury (AKI) patients remains very high, although very important advances in understanding the pathophysiology and in diagnosis and supportive care have been made. Most commonly, adverse outcomes are related to extra-renal organ dysfunction and failure. We and others have documented inflammation in remote organs as well as microvascular dysfunction in the kidney after renal ischemia. We hypothesized that abnormal microvascular flow in AKI extends to distant organs. To test this hypothesis, we employed intravital multiphoton fluorescence imaging in a well-characterized rat model of renal ischemia/reperfusion. Marked abnormalities in microvascular flow were seen in every organ evaluated, with decreases up to 46% observed 48 hours postischemia (as compared to sham surgery, p = 0.002). Decreased microvascular plasma flow was found in areas of erythrocyte aggregation and leukocyte adherence to endothelia. Intravital microscopy allowed the characterization of the erythrocyte formations as rouleaux that flowed as one-dimensional aggregates. Observed microvascular abnormalities were associated with significantly elevated fibrinogen levels. Plasma flow within capillaries as well as microthrombi, but not adherent leukocytes, were significantly improved by treatment with the platelet aggregation inhibitor dipyridamole. These microvascular defects may, in part, explain known distant organ dysfunction associated with renal ischemia. The results of these studies are relevant to human acute kidney injury.